Comparison of Two Analytical Methods used for the Measurement of Total Antioxidant Status - P.V.L.N. Srinivasa Rao; V.S.Kiranmayi; P.Swathi; L. Jeyseelan; M.M.Suchitra; Aparna R. Bitla (Journal of Antioxidant Activity, 2015)
Background: Antioxidants play an important role in maintenance of human health and prevention of disease. Effective supplementation of antioxidants requires laboratory monitoring of antioxidant status. An understanding of the methods used to determine the TAS helps in better interpretation of values obtained using a particular method and also to select a suitable method. Material and Methods: Forty subjects including 25 healthy volunteers and 15 patients diagnosed with rheumatoid arthritis were studied. All samples were analysed for TAS using Ferric reducing ability of plasma (FRAP) method and Trolox equivalent antioxidant capacity (TEAC) assay. Results: Mean TAS values obtained by TEAC method were higher than those obtained by FRAP method (p<0.0001); no difference was observed when TEAC values were corrected for proteins and FRAP values were corrected for uric acid (p=0.420). No correlation was found between TEAC and FRAP methods (p=0.102). However, when TEAC was corrected for proteins, positive correlation was observed with FRAP (p=0.044). There was agreement between the two methods when TEAC values were corrected for proteins. Conclusion: Although the reaction conditions differ, similar compounds react in both the assays and thus TEAC and FRAP assays are comparable. However, the two methods differ with respect to –SH groups and uric acid contributions. This contributes to the higher TAS values obtained by TEAC assay. Thus, in conditions with altered protein or uric acid levels, the two methods may not be used interchangeably. The TEAC assay is to be corrected for protein for comparison of reports of the two assays.
Keywords: Antioxidants